Microwave-assisted palladium-catalysed isonitrile insertion in 2-bromophenylureas for efficient synthesis of 4-substituted imino 4H-benzo[d][1, 3]oxazin-2-amines. Issue 37 (24th March 2015) - Pandey, Garima; Batra, Sanjay
Abstract : The palladium-catalysed isonitrile insertion in 2-bromophenylureas leads to the formation of 4-substituted imino 4 H -benzo[ d ][1, 3]oxazin-2-amines via C–O cross coupling reaction of the intermediate imidoylpalladium species. Abstract : A general route to the synthesis of 4-substituted imino 4 H -benzo[ d ][1, 3]oxazin-2-amines via palladium-catalysed isonitrile insertion in 2-bromophenylureas succeeded by a C–O cross-coupling of the intermediate imidoylpalladium species under microwave irradiation is reported.